THE IMPACT OF ENGLISH AS A LINGUA FRANCA ON MINORITY LANGUAGES IN UZBEKISTAN - Qo‘qonov Abdujalil (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article provides a comprehensive analysis of the impact of English as a global lingua franca on the future prospects of minority languages within the multi-ethnic linguistic landscape of Uzbekistan. The research scientifically explores the growing inter-linguistic competition, processes of linguistic assimilation, and the shrinking functional domains of local languages in the era of digital globalization. It highlights how the prestige associated with English among the younger generation poses challenges to the intergenerational transmission of heritage tongues. The author puts forward several practical recommendations for preserving linguistic diversity, maintaining a balance between global integration and national identity, and enhancing the cultural and educational status of minority languages.